AGRICULTURAL ADVISORS` ROLE IN THE USE OF ICTs AS A TOOL FOR A MORE SUSTAINABLE SERBIAN AGRICULTURE - Radovic, Vesela; Pešić, Bratislav; Filipović, Jasmina; Ćosić, Milivoje (Economics of Agriculture, 2021)
The aim of this paper was to show the role and importance of agricultural advisers in the development and implementation of information and communication technologies (ICTs) in a path to the more sustainable agriculture, and achieving the SDG2 Zero Hunger of the UN 2030 Agenda. There are a lot of challenges in the efforts to develop so-called ``hi-tech agriculture`` and smart farming in the Republic of Serbia. This research is conducted on the territory of the Nisava district in three municipalities: Merošina, Gadžin Han and Niš. The obtained data were statistically processed and presented through tables and charts. Agricultural advisors play an important role in the digital literacy of agricultural producers on their pace to implement in practice principles of hi-tech agriculture. The most important is the funding of permanent education of advisers, as well agricultural producers to acquire the state of art knowledge and experience needed to become more competitive in the EU and global market.